PENGARUH MODAL,WIRAUSAHA, PENGALAMAN DAN TEKNOLOGI TERHADAP PRODUKTIVITAS KELOMPOK WANITA TANI DI KECAMATAN PETANG - Dita Bintang, I Putu Bagus; Dewi, Ni Putu Martini (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Agriculture is still an important role in many developing countries, because this sector is a source of employment for around 60 to 70 percent of the population in most developing countries. Especially in Badung Regency, it intensively carries out guidance to community groups that carry out processing industry activities. Data collection is done by questionnaire and measurement of variables using a Likert scale model taken from the total population. Data analysis used statistical suffix with moderation regression analysis (MRA) techniques. In general, the purpose of this study is to analyze the effect of factors of production on labor productivity in the Farmer Women Group (KWT) in Petang District. The results of data analysis show that there is a significant effect of capital on labor productivity of the Kelompok Wanita Tani (KWT) in Petang District, there is a significant effect of entrepreneurship on the labor productivity of the Kelompok Wanita Tani (KWT) in Petang District, there is a significant influence of technology on labor productivity of the Kelompok Wanita Tani (KWT) in Petang District and work experience moderate the level of influence of capital, entrepreneurship and technology on the productivity of farmer women groups in Petang sub-district. Keywords: capital, entrepreneurship, experience, technology  farm productivity